1 - Introduction: Pan Africanism and the Reparative Framework for Global Africa - Horace G. Campbell (CODESRIA Bulletin, 2021)
A revolutionary future is taking place that is transforming almost every aspect of society on a global level. Africa has been engulfed by this revolutionary transformation as well as the entire African Diaspora. Of course, this means that Pan-Africanism, the discourse and action that links together Africa and the African Diaspora, is being transformed in the digital age. (Alkalimat and Williams) (this Bulletin page 49)